2019
DOI: 10.1002/prot.25748
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of molecular features for the drug discovery targeting protein‐protein interaction of Helicobacter pylori CagA and tumor suppressor protein ASSP2

Abstract: Half of the world population is infected by the Gram‐negative bacterium Helicobacter pylori (H. pylori). It colonizes in the stomach and is associated with severe gastric pathologies including gastric cancer and peptic ulceration. The most virulent factor of H. pylori is the cytotoxin‐associated gene A (CagA) that is injected into the host cell. CagA interacts with several host proteins and alters their function, thereby causing several diseases. The most well‐known target of CagA is the tumor suppressor prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Modelling procedures for protein-protein docking and interface analyses were performed as previously described (11)(12)(13). Protein surface and patch analyses were performed in MOE suit (2019.0102) as described previously (14).…”
Section: Sars-cov-2 Spike Protein and Antibody Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling procedures for protein-protein docking and interface analyses were performed as previously described (11)(12)(13). Protein surface and patch analyses were performed in MOE suit (2019.0102) as described previously (14).…”
Section: Sars-cov-2 Spike Protein and Antibody Modellingmentioning
confidence: 99%
“…After temperature and pressure equilibration, MD simulation were carried out for 30ns for each system. Detailed procedure has been described in our previous studies (12,14).…”
Section: Sars-cov-2 Spike Protein and Antibody Modellingmentioning
confidence: 99%
“…(1) the activation of the oxidant-sensitive nuclear transcriptional factor kappa B via the classic pathway and alternatively through MAPK stimulation and (2) the activation of the pathway related to transcription factor AP-1. The interaction between cytosolic nucleotide binding and oligomerization domain 1 after delivery of H. pylori peptidoglycan in host cells for both mechanisms is essential [14] Although Ando et al reported that IL-8 expression is present in CagA-negative H. pylori genotypes [15], Peng et al observed the upregulation of IL-8 expression in both strains [16].…”
Section: Caga-related Pathways H Pylori and Gastric Cancermentioning
confidence: 99%
“…The negative value of the stability indicates the more stability of the complex. Hence, a positive value of the dStability shows the importance of the particular residue in the interface region of the complex structure [20,21]. Alanine Mutagenesis studies was conducted using MOE analyse the role of specific amino acid in the stability of the DBLβ12 and gC1qR [19].…”
Section: Alanine Scanning Mutagenesis (Asm) Analyses Of Dblβ12 and Gc1qrmentioning
confidence: 99%